THE INFLUENCE OF SOCIODEMOGRAPHIC FACTORS ON KNOWLEDGE AND ATTITUDES ABOUT THE USE OF ANTIBIOTICS IN RURAL COMMUNITIES: OBSERVATIONAL STUDY IN CEMPAKA BANJARBARU DISTRICT - Rahmayanti Fitriah; Nurul Mardiati (Jurnal Farmasi Sains dan Praktis, 2021)
Antibiotics are examples of drugs that are often used incorrectly. Such misuse is often influenced by the lack of knowledge and attitudes towards the use of antibiotics, so in this study we want to know what sociodemographic factors have an influence on knowledge and attitude on antibiotic use in rural communities at Cempaka Banjarbaru District, South Kalimantan, Indonesia. This type of research is descriptive analytic with a sampling technique that is proportional stratified random sampling using a questionnaire. There are 380 respondents taken as a sample. Analysis data used is univariate and bivariate with chi-square test. The result of public knowledge research on the use of antibiotics included in the good category that is 58.2 % and attitudes included in the positive category that is 98.4 %. Statistical test results show that there is a significant influence between sociodemographic factors of recent education and income on the level of knowledge, while sociodemographic factors of age, sex and occupation on the level of knowledge have no significant effect. On the results of statistical tests sociodemographic factors (age, sex, occupation, last education and income) on attitudes do not have a significant effect.